2017
DOI: 10.1111/desc.12640
|View full text |Cite
|
Sign up to set email alerts
|

“Mummy, keep it steady”: phonetic variation shapes word learning at 15 and 17 months

Abstract: Fifteen-month-olds have difficulty detecting differences between novel words differing in a single vowel. Previous work showed that Australian English (AusE) infants habituated to the word-object pair DEET detected an auditory switch to DIT and DOOT in Canadian English (CanE) but not in their native AusE (Escudero et al., ). The authors speculated that this may be because the vowel inherent spectral change variation (VISC) in AusE DEET is larger than in CanE DEET. We investigated whether VISC leads to difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“… These vowels are also differentiated by their dynamic properties in AusE (Elvin, Williams, & Escudero, ; Escudero, Mulak, Elvin, & Traynor, ; Williams, Escudero, & Gafos, ). …”
mentioning
confidence: 99%
“… These vowels are also differentiated by their dynamic properties in AusE (Elvin, Williams, & Escudero, ; Escudero, Mulak, Elvin, & Traynor, ; Williams, Escudero, & Gafos, ). …”
mentioning
confidence: 99%
“…For instance, the F1 × F2 trajectory of AusE /iː/ begins more central and moves towards the periphery of the F1 × F2 vowel space, whereas the F1 × F2 trajectories of /ɪ/ and /ɪə/ begin more peripheral and move towards the center (Figure 1). If spectral differences between the onsets and offsets of individual vowels are assumed to be important within the NRV framework, then the bias towards peripheral vowels would mean closing vowels are perceptually more prominent than centering vowels, explaining some of the present results (for further discussion, see [27] and [28]).…”
Section: Discussionmentioning
confidence: 67%
“…The authors used acoustic analyses of the stimuli to predict that infants would be most successful at discriminating the vowel contrasts Phonetic detail in infant speech perception and word learning 8 with the largest acoustic distance, regardless of whether they were produced in their native English variety. 1 Additionally, Australian 17-month-olds succeed at discriminating both Australian English /diːt/-/duːt/ and /diːt/-/dɪt/ in the Switch task, although learning was more robust for the former contrast (Escudero, Mulak, Elvin, & Traynor, 2018). The authors reported detailed acoustic analyses that showed that the vowels in the words /diːt/, /dɪt/, and /duːt/ differed significantly in their dynamic properties.…”
mentioning
confidence: 99%
“…We hypothesised that if the acoustic properties of specific vowel contrasts do not influence phoneme discrimination during the second year of life, vowel discrimination for /diːt/-/duːt/ and /diːt/-/dɪt/ should be equally successful. Alternatively, the acoustic properties of the vowels may impact phoneme discrimination, in that the phonetic variation in the production of /diːt/, which reduces the phonetic distance between /diːt/ and /dɪt/, may make this contrast more difficult than /diːt/-/duːt/ (Escudero et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation